2022
DOI: 10.1021/acscatal.2c01772
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Phase-Controlled Synthesis of Mesoporous Molybdenum Carbides for Efficient Alkaline Hydrogen Evolution

Abstract: Transition metal carbides (TMCs) have shown great promise as nonprecious metal electrocatalysts for electrochemical energy conversion reactions owing to their Pt-like catalytic activity. The major challenges in the synthesis of TMCs include the selective formation of a catalytically active phase, enlargement of the catalytically active surface area, and control of the carbonaceous overlayer, all of which collectively influence their catalytic reactivity. Herein, we present a systematic study on the catalytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 85 publications
(124 reference statements)
0
37
0
1
Order By: Relevance
“…(e) Polarization curves of MMC‐H 2 , MMC, and 20 wt% Pt/C catalysts recorded before and after 1000 cycles between 0.1 and −0.3 V (vs. RHE). Reproduced from Baek et al 40 with permission from the ACS. (f) HRTEM image of Pt/MMC with structural model.…”
Section: Ordered Mesoporous Metal Carbides For Alkaline Hermentioning
confidence: 99%
See 2 more Smart Citations
“…(e) Polarization curves of MMC‐H 2 , MMC, and 20 wt% Pt/C catalysts recorded before and after 1000 cycles between 0.1 and −0.3 V (vs. RHE). Reproduced from Baek et al 40 with permission from the ACS. (f) HRTEM image of Pt/MMC with structural model.…”
Section: Ordered Mesoporous Metal Carbides For Alkaline Hermentioning
confidence: 99%
“…Inspired by these results, we attempted to prepare a large surface area metastable α ‐MoC 1− x material to boost the alkaline HER activity 40 . Toward realizing this goal, nanocasting again proved to be a versatile method.…”
Section: Ordered Mesoporous Metal Carbides For Alkaline Hermentioning
confidence: 99%
See 1 more Smart Citation
“…The support has the role of dispersing and anchoring the active component, and the interaction force between different supports and the active component varies; thus, the choice of support is equally important. Carbides have been widely studied as typical electrocatalytic supports, 23,24 including carbides such as Mo 2 C, 25–28 WC, 29,30 TiC, 31 and Ni 3 C; 32 they have stronger interactions with metals than carbon, 33 and can provide stronger interaction forces. Among them, boron carbide (B 4 C) is a nonmetallic carbide; it is one of the most stable substances toward acid and has the advantages of a high melting point and good electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Mo y C can be stabilized into several phases including α-Mo 2 C, β-Mo 2 C, α-MoC, γ-MoC, δ-MoC, and η-MoC. Among these phases, β-Mo 2 C is found to be the most catalytically active phase. , In a previous study, we showed that the active sites of β-Mo 2 C originate from the (011) surface that exposes Mo–C atoms, as it has low surface energy and can bind hydrogen optimally . In the last few years, considerable attention has been devoted to further improving the HER efficiency of Mo y C catalysts via a complex nanostructuring approach that involves a hybrid of several mechanisms.…”
Section: Introductionmentioning
confidence: 99%